Elevating the discourse on experience in healthcare’s uncertain times - Jason Wolf (The Beryl Institute, 2018)
Over the last five years, we have been inspired by the breadth of contributions that have helped shape the experience landscape through PXJ as well as the reach that the conversation on patient experience has had. Both the authors and readers of PXJ reinforce that the conversation on patient experience and the human experience in healthcare is not one dominated by national intent or even policy. While for some motivation has come in some part from mandated action, for most tackling this idea in healthcare is it grounded in two core realities. The first, in healthcare at its core we remain committed to ensuring the best for those we serve as active and engaged people, not simply as passive participants in care. This requires a different way of thinking and doing than a simple model for throughput or a checklist mentality. The complexity of the humanity at the heart of healthcare perhaps is also its greatest strength. In acknowledging the humanity of healthcare, we breathe life into our organizations, we excavate lost purpose in burned out and fatigued practitioners and we give permission to connect with others. This connection is not simply in the buildings we find ourselves, but it is our humanity that links us across communities and countries, continents and oceans. This connection and the conversation that supports it will forever be the grounds on which healthcare will ultimately succeed, it is the foundation on which we can and must elevate the discourse on experience.